Familial and lifestyle factors related to physical activity in elementary school students: a cross-sectional study based on a nationally representative survey in Japan - Noriko Motoki; Haruka Morota; Takumi Shibazaki; Chizuko Nakamura; Yozo Nakazawa (BMC, 2023)
Abstract Purpose The decrease in physical activity (PA) among children has become a global concern. Since the analysis of sociodemographic factors as determinants of exercise habits has been inconclusive, this study investigated the factors related to participation in organized sports and moderate-to-vigorous PA (MVPA) levels. Methods Cross-sectional data from the Sports-Life Survey conducted in 2019 by the Sasagawa Sports Foundation were used. Data on the gender, age, grade, annual household income, family members, and lifestyle habits of elementary school children as well as information on participation in organized sports and MVPA were collected by written questionnaires. Multiple logistic regression models were applied to calculate the adjusted odds ratio and 95% confidence interval for the association of each variable with participation in organized sports and frequent MVPA (≥ 60 min/day for ≥ 5 days/week). Results A total of 1,197 participants were included in the analysis. Whereas 1,053 (88.2%) students expressed a like for PA, only 725 students (60.8%) actually took part in organized sports. Organized sports participation was significantly associated with gender, grade, population density, household income, daily breakfast, lower screen time, and frequent exercise with parents (all P < 0.05). We observed that 12.3% of participants met the frequent MVPA level, which was significantly related to lower screen time and exercise habits with parents (both P < 0.05). Conclusions Social and family factors may be strong determinants of engagement in PA among Japanese elementary school-aged children. Parental involvement appears particularly important for promoting PA among youths.